Developing Vocabulary Game through “Eclipse Crossword” - hesty puspota sari; Nanik Sri Rahayu; Julia Ike Darmayanti (EDUCATIO : Journal of Education, 2022)
This research is aimed to develop a vocabulary game by utilizing an eclipse crossword web application. It is done to motivate the third-semester students of Baltar Islamic University in learning vocabulary. This research is Research and Development (R&D), which used the ADDIE’s model. It consists of analyzing, designing, developing, implementing, and evaluating. This means, at the end of the research, a specific product is produced. It is a puzzle game through eclipse crossword which can be used in the learning process and overcome the students’ problems with vocabulary lack. The data was collected through interviews, questionnaires, documentation, and test. The result of the research showed that the result for all validation was 88%. The score was categorized as “very good” with intervals 80% < x ≤ 100%. So, the development of a vocabulary game through eclipse crossword for learning vocabulary was valid to be implemented for the third-semester students of Islamic Balitar University. So, in another word the students absolutely agree with using an eclipse crossword in learning vocabulary.